The Impact of Leadership Communication and Empowerment on Job Motivation Amongst Public Sector Employees in Malaysia - Wan Mohd Amin, Wan Abd Aziz; Muda, Mohd Shaladin; Omar, Nik Wan (Universiti Utara Malaysia Press, 2006)
This paper describes a research project that investigated the influence of leadership communication and staff empowerment on job motivation among civil servants. The aim was to fill a gap in the management literature, especially in the Malaysian perspective under the dynamic context of the recent civil servant empowerment practices between state and federal agency departments. Three dimensions on leadership communication had been examined, namely, initiating structure, consideration, and communication orientation, and their link with empowerment and job motivation. A face-to-face survey was performed on 198 respondents from five state agency departments and five federal agency departments using a stratified random sampling technique. As well as the importance of literature contribution, some of the conclusions from this study can give an important insight for the Malaysian practitioners in public sector management. Part of the conclusion suggests that the consideration dimension is proven to be able to encourage empowerment practice and consequently would increase staff motivation. Another finding is that leadership communication based on the three dimensions above is better practised in the federal agencies than the state agencies. The study also proved that leadership communication, empowerment, and forecast factors would contribute toward the increase of motivation among workers.